A Review on Solvent-free Methods in Organic Synthesis - Zangade, Sainath; Patil, Pravinkumar (Current Organic Chemistry, 2019)
Most of the synthetic chemical transformation reactions involve the use of different organic solvents. Unfortunately, some of these toxic solvents are used in chemical laboratory, industry and have been considered a very serious problem for the health, safety of workers and environmental damage through pollution. The purpose of green chemistry is to provide a path that reduces or eliminates the use of such hazardous toxic solvents. Therefore, the key factor of the green synthetic approach is to utilize renewable materials, nontoxic chemical and to perform the reactions under solvent-free conditions. In this review, we have discussed most recent literature survey on applications of solvent-free techniques in organic synthesis which would offer a new opportunity to a researcher to overcome the problem of using environmental harmful solvents.
Keywords: microwave irradiation